The Role of Maqasid Al-Shariah and Maslahah in Ethical Decision Making: A Study of Professionals in Indonesia - Sudarmawan Samidi; Mohammad Faby Rizky Karnadi; Dety Nurfadilah (International Journal of Business Studies, 2018)
Ethical behavior is very important for every professional to ensure that the business will sustain for a long time and gain proitable. The present study is aimed at understanding the importance of Maqasid Al-Shariah and Maslahah in making ethical decisions among executive professionals in Indonesia. In view of this, the research explore to extent to which practitioners understand the concept of Maqasid Al-Shariah and Maslahah concept in making ethical decisions, and whether there is a relationship between their understanding of the concept and ethical decisions. Qualitative research method is used to collect a data from seven executiveprofessionals from different industry and working experiences. This study used in-depth and intensive semi-structured interview. The finding showed that majority ofrespondents are not familiar with the concept of Maqasid Al-Shariah and Maslahah, although they proved that their current practice actually has been part ofthis concept.